Deconstructing symbolic consumption: exploring the anti-synthetic space between meaning and meaninglessness. Issue 3 (4th May 2017) - Lanier, Clinton D.; Rader, C. Scott
ABSTRACT: Meaning is a fundamental aspect of symbolic consumption and lies at the heart of consumer culture theory (CCT). Although consumption meanings are considered dynamic, heterogeneous, and contextual, meaning itself is considered an inherent aspect of consumer culture and a constitutive force of consumer experiences. Utilizing deconstruction as a critical strategy, this paper interrogates the concept of meaning in the CCT literature and contends that meaning is not only present in consumption practices, but it is also absent. As meaning circulates in the infinite possibilities of language, meaninglessness emerges as an important aspect of this process. The dialectical tension between meaning and meaninglessness, though, does not converge within a particular consumption practice, but continuously diverges in the anti-synthetic space between them. We empirically explore the consumption of this anti-synthetic space in three popular culture exemplars. We conclude by discussing the broader implications of the deconstruction of symbolic consumption for CCT.